Multi‐faceted Set‐up of a Diverse Ketoreductase Library Enables the Synthesis of Pharmaceutically‐relevant Secondary Alcohols. Issue 6 (22nd January 2021) - Voss, Moritz; Küng, Robin; Hayashi, Takahiro; Jonczyk, Magdalena; Niklaus, Michael; Iding, Hans; Wetzl, Dennis; Buller, Rebecca
Abstract: Enzymes are valuable tools to introduce chirality into small molecules. Especially, ketoreductase (KRED)‐catalyzed transformations of ketones to yield chiral secondary alcohols have become an established biocatalytic process step in the pharmaceutical and fine chemical industry. Development time, however, remains a critical factor in chemical process development and thus, the competitiveness of a biocatalytic reaction step is often governed by the availability of off‐the‐shelf enzyme libraries. To expand the biocatalytic toolbox with additional ketoreductases, we established a multi‐faceted screening procedure to capture KRED diversity from different sources, such as literature, available genome data, and uncharacterized microbial strains. Overall, we built a library consisting of 51 KRED enzymes, 29 of which have never been described in literature before. Notably, 18 of the newly described enzymes exhibited anti‐Prelog preference complementing the majority of ketoreductases which generally follow Prelog's rule. Analysis of the library's catalytic activity toward a chemically diverse ketone substrate set of pharmaceutical interest further highlighted the broad substrate scope and the complementing enantio‐preference of the individual KREDs. Using the generated sequence‐function data of the included short chain dehydrogenases in a bioinformatic analysis led to the identification of possible sequence determinants of the stereospecificity exhibited by these enzymes. Abstract : Ketoreductases : The availability of ready‐to‐screen enzyme libraries enables the identification of suitable biocatalysts early in process design and accelerates the implementation of biocatalytic steps in industry. Here, we present a panel of 51 ketoreductases and showcase its ability to synthesize valuable building blocks. The identified protein sequence pattern linked to the enzymes' enantioselectivities is expected to guide future enzyme sourcing campaigns.